MEMBANGUN PROFESIONALISME GURU YANG HUMANIS DALAM MENYAMBUT KURIKULUM NASIONAL - Asfiati, Asfiati (FORUM PAEDAGOGIK, 2016)
Education is one aspect of human development index (HDI) developed by the United Nations Development Programs (UNDP). For the entire educational potential should be aimed at achieving the level of progress the development of a solid education, both quantitatively and qualitatively. Education, becomes the standard is used in the printing of human resources (HR) will be superior and competitive by building a professional teacher. Teachers who understand all the meaningfulness known as humanist professional teachers.Humanists professional teachers have a social responsibility, and a sense of togetherness with learners. Humanist professionalism of teachers show the students that the teacher is able to recognize that learners have special missions to develop their potential. Humanists professionalism of teachers provide opportunities for learners in building a profitable learning in order to create learning that reaches the point of togetherness. It is together in achieving the core activities and to examine the material together.Humanists professional teachers state that the learning approach is seen as a private act to fulfill the potential of learners. Through the professional teachers can succeed in the success of the national curriculum. Teacher is the operator of the educational curriculum. The national curriculum being part made in achieving the national curriculum itself through curriculum-based development, and curriculum specificities/conditions in their respective educational institutions.